2012
DOI: 10.1002/micr.22064
|View full text |Cite
|
Sign up to set email alerts
|

Free fasciocutaneous flaps for reconstruction of complete circumferential degloving injury of digits

Abstract: Complete circumferential degloving injury of the digits usually results in a large cutaneous defect with tendinous structure and bone and joint exposure. When revascularization is not possible, a thin and adequately sized flap is required to resurface the defect, restore finger function, and prevent amputation. In this report, we present our experience with reconstruction of the entire circumferential degloving injury of the digits using free fasciocutaneous flaps. Between February 2006 and January 2011, 9 mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
(59 reference statements)
0
24
0
Order By: Relevance
“…In the textbook on perforator flaps, Schoeller et al wrote a section titled “S‐FAP flap”; however, the flap they described was based on the medial descending branch of the lateral circumflex femoral artery and was not the S‐FAP flap . Hayashi and Maruyama did not differentiate the S‐FAP flap from a flap based on the lateral circumflex femoral artery and lumped them together under the name “anteromedial thigh flap.” Lin et al reported the use of a free anteromedial thigh flap for digital reconstruction; however, the source vessel of the perforator was not described . Their flap designs were similar to ours; however, their flaps could not be classified because detailed anatomic information about the perforators was not provided.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In the textbook on perforator flaps, Schoeller et al wrote a section titled “S‐FAP flap”; however, the flap they described was based on the medial descending branch of the lateral circumflex femoral artery and was not the S‐FAP flap . Hayashi and Maruyama did not differentiate the S‐FAP flap from a flap based on the lateral circumflex femoral artery and lumped them together under the name “anteromedial thigh flap.” Lin et al reported the use of a free anteromedial thigh flap for digital reconstruction; however, the source vessel of the perforator was not described . Their flap designs were similar to ours; however, their flaps could not be classified because detailed anatomic information about the perforators was not provided.…”
Section: Discussionmentioning
confidence: 70%
“…11 Lin et al reported the use of a free anteromedial thigh flap for digital reconstruction; however, the source vessel of the perforator was not described. 12 Their flap designs were similar to ours; however, their flaps could not be classified because detailed anatomic information about the perforators was not provided.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, we decided to reconstruct with a flap. There are many other flaps for reconstruction of this case including local/distant flaps and free flaps such as medial plantar flap, medialis pedis flap, and venous flap, that we offered as reconstructive options before the treatment . Because the patient desired a concealable donor site with less morbidity, we decided to use a flap from the lower‐abdominal/inguinal region.…”
Section: Discussionmentioning
confidence: 99%
“…There are many other flaps for reconstruction of this case including local/distant flaps and free flaps such as medial plantar flap, medialis pedis flap, and venous flap, that we offered as reconstructive options before the treatment. [10][11][12] Because the patient desired a concealable donor site with less morbidity, we decided to use a flap from the lower-abdominal/inguinal region. SCIP flap and SIEA flap have a long pedicle suitable for various reconstructions, and their donor scars are well-concealable.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Among many options of treating a degloving injury are: salvaging the degloved segment through conservative therapy with dressing, debriding and skin grafting, maintaining vascularity by arterial anastomosis or arteriovenous shunting; and coverage by free flaps if the segments are not salvageable. [3][4][5] The traditional approach to the circumferentially degloved segment of problematic flap viability has been to resuture the flap and to wait and see. However, the waiting period or the specific treatment protocol remains uncertain.…”
mentioning
confidence: 99%